Psychotropic medication use and Parkinson's disease risk amongst older women - Hind A. Beydoun; Nazmus Saquib; Robert B. Wallace; Jiu‐Chiuan Chen; Mace Coday; Michelle J. Naughton; May A. Beydoun; Aladdin H. Shadyab; Alan B. Zonderman; Robert L. Brunner (Annals of Clinical and Translational Neurology, 2022)
Abstract Objective To examine associations of antidepressant, anxiolytic and hypnotic use amongst older women (≥65 years) with incident Parkinson's Disease (PD), using data from Women's Health Initiative linked to Medicare claims. Methods PD was defined using self‐report, first diagnosis, medications and/or death certificates and psychotropic medications were ascertained at baseline and 3‐year follow‐up. Cox regression models were constructed to calculate adjusted hazard ratios (aHR) with 95% confidence intervals (CI), controlling for socio‐demographic, lifestyle and health characteristics, overall and amongst women diagnosed with depression, anxiety and/or sleep disorders (DASD). Results A total of 53,996 WHI participants (1,756 PD cases)—including 27,631 women diagnosed with DASD (1,137 PD cases)—were followed up for ~14 years. Use of hypnotics was not significantly associated with PD risk (aHR = 0.98, 95% CI: 0.82, 1.16), whereas PD risk was increased amongst users of antidepressants (aHR = 1.75, 95% CI: 1.56, 1.96) and anxiolytics (aHR = 1.48, 95% CI: 1.25, 1.73). Compared to non‐users of psychotropic medications, those who used 1 type had ~50% higher PD risk, whereas those who used ≥2 types had ~150% higher PD risk. Women who experienced transitions in psychotropic medication use (‘use to non‐use’ or ‘non‐use to use’) between baseline and 3‐year follow‐up had higher PD risk than those who did not. We obtained similar results with propensity scoring and amongst DASD‐diagnosed women. Interpretation The use of antidepressants, anxiolytics or multiple psychotropic medication types and transitions in psychotropic medication use was associated with increased PD risk, whereas the use of hypnotics was not associated with PD risk amongst older women.